2022
DOI: 10.21203/rs.3.rs-2142080/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basement membrane genes can predict the prognosis of patients with clear cell renal cell carcinoma (ccRCC) and are correlated with immune status

Abstract: Background: Basement membrane (BM) genes are an important factor in the process of clear cell renal cell carcinoma (ccRCC). Thus, identifying BMs with prognostic values in ccRCC is critical. Methods: The samples from TCGA were separated randomly into 2 cohorts, the training cohort, and the validation cohort. For the training cohort univariate Cox, Lasso, and multivariate Cox regression analyses were applied to identify prognostic BM genes and then construct a prognostic BM-genes’ signature. The nomogram was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recently, we have shown that, for most cancers, survival prediction can be improved by incorporating clinical and transcriptomic data [20]. Additionally, there is an increasing interest in how ECM-related genes could be used to assess the survival of ccRCC patients [21][22][23][24]. To the best of our knowledge, COL7A1 expression in ccRCC was not investigated as an independent prognostic biomarker in this disease, and this is the first ccRCC study using five independent public datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that, for most cancers, survival prediction can be improved by incorporating clinical and transcriptomic data [20]. Additionally, there is an increasing interest in how ECM-related genes could be used to assess the survival of ccRCC patients [21][22][23][24]. To the best of our knowledge, COL7A1 expression in ccRCC was not investigated as an independent prognostic biomarker in this disease, and this is the first ccRCC study using five independent public datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that, for most cancers, survival prediction can be improved by incorporating clinical and transcriptomic data [17]. Additionally, there is an increasing interest in how ECM-related genes could be used to assess the survival of ccRCC patients [18][19][20][21]. To the best of our knowledge, COL7A1 expression in ccRCC was not investigated as an independent prognostic biomarker in this disease.…”
Section: Introductionmentioning
confidence: 99%